2012
DOI: 10.1345/aph.1r174
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitor Use and Association with Spontaneous Bacterial Peritonitis in Patients with Cirrhosis and Ascites

Abstract: Patients with cirrhosis and ascites should be monitored carefully while on PPIs for a possible increased risk of infection from spontaneous bacterial peritonitis and C. difficile. Prospective randomized trials are needed to confirm this association. Clinicians should be aware of this lesser known adverse effect of PPIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The potential clinical consequences could be increased incidences of enteric infections [ 4 ], including Clostridium difficile enterocolitis, and pulmonary infections [ 7 ]. Some specific subsets of patients could sustain a particularly high risk of suffering these complications, including cirrhotics with ascites [ 16 , 17 ] and hospitalized patients on antibiotic therapy [ 6 ]. CKD may also represent a high risk setting, because the intestinal barrier and the microbiota of these patients are frequently altered [ 18 ], and treatment with IGAS could further complicate these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The potential clinical consequences could be increased incidences of enteric infections [ 4 ], including Clostridium difficile enterocolitis, and pulmonary infections [ 7 ]. Some specific subsets of patients could sustain a particularly high risk of suffering these complications, including cirrhotics with ascites [ 16 , 17 ] and hospitalized patients on antibiotic therapy [ 6 ]. CKD may also represent a high risk setting, because the intestinal barrier and the microbiota of these patients are frequently altered [ 18 ], and treatment with IGAS could further complicate these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In cirrhotic patients, the main reason for inadequate PPI use was previous variceal bleeding (Kalaitzakis and Björnsson, 2008). Although clinical guidelines recommended PPI administration prior to endoscopic variceal ligation, this is not reasonable for continuous long-term PPI therapy (Garcia-Tsao et al, 2007;Siple et al, 2012). Acid secretion is constitutively reduced during cirrhosis, so there is no sufficient evidence to support PPI use for prophylaxis of peptic complications in patients with portal hypertension or esophageal varices (Merli et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the studies about the effect of PPIs on bacterial translocation were limited to animal studies. Recently published studies have suggested that PPIs could increase the risk of SBP in patients with cirrhosis (11, 12, 16, 25, 26). The use of PPIs increases the gastric pH, bacterial translocation, facilitates the growth of the gut microflora, and alters various immunomodulatory and anti-inflammatory effects (12, 27).…”
Section: Discussionmentioning
confidence: 99%
“…Previous case control studies have found an increased risk of GI infections in patients taking PPIs (10). Some studies have reported that PPI therapy is associated with spontaneous bacterial peritonitis (SBP) in patients with advanced cirrhosis (11, 12). Increased ammonia-producing enteric bacteria in patients is shown to be a risk factor for HE (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation